1995
DOI: 10.1097/00000539-199508000-00016
|View full text |Cite
|
Sign up to set email alerts
|

The Optimal Distance That a Multiorifice Epidural Catheter Should Be Threaded into the Epidural Space

Abstract: Complications can occur during epidural placement for women in labor. As many as 23% of epidural anesthetics may not provide satisfactory analgesia. The cause of this may be technical. This study was undertaken to determine the optimal distance that a multiorifice catheter should be threaded into the epidural space to maximize analgesia and minimize complications. One hundred women in labor were enrolled in this prospective, randomized, and double-blind study. Patients were randomly assigned to have the epidur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 79 publications
(43 citation statements)
references
References 10 publications
0
40
1
Order By: Relevance
“…Cesur et al [6] reported an 8.2% incidence of intravascular placement with 3-cm catheter insertion in normal healthy adult patients, while Beilin et al [8] reported an 8.3% incidence of intravascular location in healthy parturients, with the highest frequency occurring in the 7-cm group, as compared to a 7.5% incidence of intravascular placement in our study. Beilin et al [8] had performed aspiration to rule out intravascular placement after the entire 7 cm had been advanced into the epidural space.…”
Section: Discussioncontrasting
confidence: 50%
See 4 more Smart Citations
“…Cesur et al [6] reported an 8.2% incidence of intravascular placement with 3-cm catheter insertion in normal healthy adult patients, while Beilin et al [8] reported an 8.3% incidence of intravascular location in healthy parturients, with the highest frequency occurring in the 7-cm group, as compared to a 7.5% incidence of intravascular placement in our study. Beilin et al [8] had performed aspiration to rule out intravascular placement after the entire 7 cm had been advanced into the epidural space.…”
Section: Discussioncontrasting
confidence: 50%
“…Beilin et al [8] had performed aspiration to rule out intravascular placement after the entire 7 cm had been advanced into the epidural space. It is possible that intravascular placement had occurred earlier and it was only by chance that these patients were part of the 7-cm group.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations